Implementing the PDCA-Based Human Resource Management Model to Enhance Teacher Performance - Rishawarti Anggraeni; Waska Warta (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
This study investigates the implementation of human resource management (HRM) practices based on the Plan-Do-Check-Act (PDCA) cycle to enhance teacher performance in two Indonesian elementary schools: SDN Jatisari and SDN Cimuncang, located in Baleendah District. Employing a qualitative descriptive design, the research explores how HRM processes—including planning, implementation, evaluation, and follow-up—are executed and the challenges encountered in each stage. Data were collected through in-depth interviews, participatory observation, and document analysis, with triangulation applied to ensure validity. The findings reveal that HRM implementation in both schools has followed the PDCA framework but remains suboptimal in effectiveness. In the planning stage, teacher participation is limited, and most decisions are made through a top-down approach. The implementation stage exhibits mismatches between teachers’ qualifications and teaching assignments, alongside irregular professional development programs. Evaluation processes lack standardized performance assessment instruments, leading to inconsistent and subjective feedback. Furthermore, the follow-up stage shows weak monitoring mechanisms and fragmented post-training evaluations, mainly due to financial constraints. Despite these limitations, the application of PDCA principles has provided both schools with a foundational structure for continuous improvement. The research concludes that effective HRM practices require an integrated, participatory, and data-driven approach aligned with Total Quality Management (TQM) principles. Strengthening teacher involvement, establishing standardized evaluation systems, and institutionalizing continuous monitoring are critical to enhancing teacher performance and improving educational quality. This study contributes theoretically by contextualizing the PDCA cycle within HRM for primary education and practically by offering actionable strategies for school leaders to implement sustainable HRM reforms in Indonesian elementary schools.